Evaluation of apartement development policy: Case study of implications for Malang City regional spatial planning (2018-2020) - Behiningan, Abd Fatah Alaudin; Darajad, Syarifuddin (Universitas Islam Malang, 2024)
This study examines the compatibility of the Malang City Spatial Plan with the Begawan Apartment development and its resulting impacts. The RTRW aims to establish spatial patterns based on principles such as integration, harmony, sustainability, usability, openness, justice, and accountability. Using a qualitative descriptive approach, the research involved interviews with the Malang City Department of Manpower, Investment, and Comprehensive Services, the Begawan Apartment director, and residents of Tlogomas Village (RW 5 and RW 7). Analysis was conducted through William Dunn’s public policy framework to assess Malang City's regulations on apartment construction. Findings indicate that while no specific regulations govern Begawan Apartments, it has obtained a construction permit. The development has led to negative effects, including reduced green space crucial for rainwater absorption and air quality improvement, conflicting with regulations designating the Brantas River area as green space. However, positive impacts include economic benefits for local SMMEs and increased job opportunities for residents.